FUNDAMENTALISME DAN GERAKAN POLITIK IDENTITAS - Kholid Mawardi (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2013)
AbstractViolence is not the monopoly of religious radical groups, but also in otherfields. For example sports, especially soccer, has spawned radical movements thatalso frequent violence in the name of exclusivity group, which known ashooligans supporters groups.Violence which on behalf of ethnic also occurred in Africa, as it did in1959 and 1994, where clashes between Hutus by Tutsis Tribes that resulted inthousands and even millions of Tutsis were killed. This paper intends to describethe fundamentalism, how its emergence, its characteristics, and the spread of theirparts of the world.Fundamentalism is a radical views and attitudes, militant, narrow-minded ,excited in excess (ultra - jealous) or have a tendency to achieve goals with violentmeans, thereby actually radicalism and terrorism intertwined in it.